Woody Goldenrod, Chrysoma pauciflosculosa - Debbie Miller; Mack Thetford; Chris Verlinde; Gabriel Campbell; Ashlynn Smith (EDIS, 2018)
Woody goldenrod is found in beach dunes, scrub, and sandhill plant communities. It occurs in the Panhandle of Florida and more broadly in the southeastern United States west to Mississippi and northeast to North Carolina. This plant may leach chemicals into the soil that inhibit seed germination of gulf bluestem (Schizachyrium scoparium var. scoparium) (Fischer et al. 1994). Woody goldenrod is an underused landscape plant with a prolific fall color from flowers that attract numerous pollinators. https://edis.ifas.ufl.edu/sg165